THE EFFECT OF COMMODITY PRICES, PROFITABILITY, AND LEVERAGE ON STOCK PRICES IN PALM OIL INDUSTRY COMPANIES - Nur Afni Yunita; Rany Gesta Putri Rais; Indrayani; Mursidah; Anisa Zulhikmah (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2026)
This study analyzes the effect of commodity prices, profitability, and leverage on stock prices. The sample of this study consists of 21 palm oil plantation companies listed on the Indonesia Stock Exchange during the 2022–2024 period, selected using the purposive sampling method. The analytical method employed is panel data regression. The results show that commodity prices do not have a significant effect on stock prices, while profitability and leverage have a positive and significant effect on stock prices.